The Encyclopedia of Applied Linguistics 2012
DOI: 10.1002/9781405198431.wbeal0557
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Learning

Abstract: Along with the important objective of communicative competence in foreign‐language learning, intercultural learning has been emphasized, especially since the 1980s, as a main objective of foreign and second language pedagogy (Bredella & Christ, 1995; Hu & Byram, 2009a).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…. ] outside perspective means that the other's culture is always seen through one's own eyes and understood based on one's unavoidable preconceptions" [45] (p. 2778). In this approach, Bredella et al [44] (2000) identified different forms of relationality between inside and outside perspectives.…”
Section: Competency Model For Perspective-taking In Geography Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…. ] outside perspective means that the other's culture is always seen through one's own eyes and understood based on one's unavoidable preconceptions" [45] (p. 2778). In this approach, Bredella et al [44] (2000) identified different forms of relationality between inside and outside perspectives.…”
Section: Competency Model For Perspective-taking In Geography Educationmentioning
confidence: 99%
“…In this way, ethical principles can also be discussed and reflected upon [79] (pp. [45][46][47][48], promoting tolerance of ambiguity and democratic education [28] (p. 3).…”
Section: Dimension: Evaluationmentioning
confidence: 99%
See 1 more Smart Citation